After diffusion: Challenges to enforcing nonproliferation and disarmament norms. Issue 3 (3rd July 2018) - Knopf, Jeffrey W.
ABSTRACT: This article discusses six challenges to enforcing norms regarding nuclear weapons. Three challenges reflect generic problems in international politics. These are differences in power, the collective action problem, and trade-offs with other interests. Three additional dilemmas reflect specific characteristics of the nuclear realm. First, membership in international treaties connected to the norms is not universal, raising questions about the appropriateness of enforcement against states that have not signed the treaties. Second, different implications of the norms can come into conflict with each other. In particular, there can be tensions between the requirements of nonproliferation and disarmament norms. Finally, some common options for norm enforcement become quite problematic when dealing with nuclear weapons. For example, if states respond to defections by starting their own nuclear weapons programs, this tit-for-tat response would defeat the purposes of the nonproliferation regime. Despite these challenges, nuclear norms enjoy widespread support and some enforcement is possible.